2005
DOI: 10.1111/j.1365-313x.2005.02409.x
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear gene HCF107 encodes a membrane‐associated R‐TPR (RNA tetratricopeptide repeat)‐containing protein involved in expression of the plastidial psbH gene in Arabidopsis

Abstract: SummaryExpression of the genes of plastidial psbB operon (psbB-psbT-psbH-petB-petD) involves multiple processing events and formation of several mono-, di-and multi-cistronic transcripts which are further regulated by differential stability and expression. Here we describe the identification of the HCF107 gene that is involved in the 5¢-end processing/stability and/or translation of the psbH gene and in the translation of the psbB gene. HCF107 is an RNA-TPR-containing protein with 11 RTPRs that are tandemly ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 52 publications
1
58
0
Order By: Relevance
“…Crystal structures of CstF-77 confirmed that HAT repeat tracts adopt a TPR-like structure (3,4). The possibility that HAT repeat tracts might bind RNA has been suggested (1,(5)(6)(7), but the notion that HAT repeat tracts serve as a scaffold for binding other proteins dominates recent literature (3,(8)(9)(10). This view is reflected by the annotation of the HAT motif at InterPro, which states only that "the repeats may be involved in protein-protein interactions" (http://www.ebi.…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…Crystal structures of CstF-77 confirmed that HAT repeat tracts adopt a TPR-like structure (3,4). The possibility that HAT repeat tracts might bind RNA has been suggested (1,(5)(6)(7), but the notion that HAT repeat tracts serve as a scaffold for binding other proteins dominates recent literature (3,(8)(9)(10). This view is reflected by the annotation of the HAT motif at InterPro, which states only that "the repeats may be involved in protein-protein interactions" (http://www.ebi.…”
mentioning
confidence: 63%
“…Mutations in Arabidopsis HCF107 cause defects in the translation and stabilization of mRNAs derived from the chloroplast psbH gene (6,15). Our results show that HCF107 binds ssRNA with specificity for sequences at the 5′ end of the processed psbH mRNA isoforms that require HCF107 for their accumulation.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Indeed, we found the closest paralog of Mac1 in Chlamydomonas to be Mbb1, a TPR/HAT repeat protein involved in the stabilization or maturation of the psbB/T and psbH mRNAs (Vaistij et al, 2000a;Loizeau et al, 2014) (Supplemental Figure 3 and Supplemental Data Set 1). The ortholog of Mbb1 in vascular plants, HCF107, is required for the stability of psbH transcripts (Felder et al, 2001;Sane et al, 2005;Hammani et al, 2012).…”
Section: Identification Of Mac1mentioning
confidence: 99%